Law No. 75 of the year 2017 On Amending Certain Provisions of Law No. 34 of the Year 1976 On the Commercial Register = قانون رقم 75 لسنة 2017 بتعديل بعض أحكام القانون رقم 34 لسنة 1976 فى شأن السجل التجارى - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic